Analysis of Watchkeeping Implementation During Cargo Lifting Operations to Avoid Collision with Rig Legs: A Case Study of AHTS Logindo - Zulkifli, Idham Abdul Aziz; Yuda, Anak Agung Ngurah Ade Dwi Putra; Arisusanty, Dian Junita; Huda, Samsul (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The operational integrity of Anchor Handling Tug Supply (AHTS) vessels during cargo lifting operations near offshore drilling rigs represents a critical intersection of navigational safety, human factors, and environmental management. This study examines the implementation of watchkeeping practices on board the AHTS Logindo Stamina while operating at the Soehanah Rig in the Natuna Sea, with particular emphasis on mitigating collision risks with rig legs. A descriptive qualitative approach was employed, drawing data from participant observation, document analysis, and semi-structured interviews with deck and bridge officers. Root causes of operational vulnerabilities were analyzed using the Fishbone (Ishikawa) Diagram across five domains: Man, Method, Machine, Environment, and Management. The findings indicate that although the vessel operates under an established Safety Management System (SMS), watchkeeping effectiveness is often reduced by human factors, including cognitive fatigue and divided attention during complex, multi-task operations. In addition, gaps were identified in the practical application of Standard Operating Procedures (SOPs), particularly in close-quarters communication between bridge and deck teams. Environmental factors, such as hydrodynamic interactions in proximity to the rig structure, further increase station-keeping demands beyond the optimal performance of Dynamic Positioning (DP) systems alone. The study concludes that collision prevention requires a shift from passive monitoring to active and predictive watchkeeping, supported by targeted navigational checklists and strengthened Bridge Resource Management (BRM) practices. These findings contribute to the enhancement of offshore operational safety and provide practical insights for reducing high-risk maritime incidents.